Strategic Alliance Implementation In the Development of Wellness Tourism Trends (Case Study of Putri Kedaton Yogyakarta Indonesia) - Warih Wulandari, Lastiani (Asian Journal of Social and Humanities, 2024)
The growing demand for health tourism presents significant opportunities for tourism players around the world. This paper examines business ethics in the implementation of strategic alliances as an important response to capitalize on the current emerging trend of Health Tourism. Based on case studies and relevant literature, this research employs a qualitative approach using descriptive analysis to investigate the benefits and challenges associated with forming alliances in the health tourism landscape as a form of corporate responsibility towards ethical business. Data is collected through literature reviews, case study analysis, and in-depth interviews with stakeholders, including healthcare providers, tourism operators, and alliance managers. Key focus areas include the co-creation of healthcare products and services and how companies conduct their business with strategic alliances. In addition, we also analyze the critical factors for successful alliance formation and management, emphasizing collaborative governance, transparent communication, and risk-sharing mechanisms by applying ethics in business. Through this exploration, the authors provide valuable insights for stakeholders looking to utilize strategic alliances in navigating the dynamic and profitable world of wellness tourism with business ethics in mind.